Grip strength mediates the relationship between muscle mass and frailty. Issue 2 (26th December 2019) - Choe, Yu‐Ri; Jeong, Ju‐Ri; Kim, Yeon‐Pyo
Abstract: Background: Although sarcopenia and frailty are important diseases in geriatrics, few studies have investigated the association between the two diseases. Thus, this study aimed to examine the relationship between two components of sarcopenia (muscle mass and muscle function) and frailty. Methods: In total, 997 Korean older adults (456 men and 541 women) were included in this cross‐sectional observational study. We used a polynomial linear regression analysis to obtain standardized sex, age, and height‐adjusted appendicular skeletal muscle mass (zASM), as well as to standardized sex, age, and height‐adjusted grip strength (zGS). We then performed a causal mediation analysis to confirm the relationship between zASM and frailty. Results: In both men and women, zGS mediated the relationship between zASM and frailty (average causal mediation effect in men: −0.096 {−0.159 to −0.050}; in women: −0.053 {−0.098 to −0.010}). For every one‐point increase in zGS score, the relative risk of a one‐point increase in frailty was reduced by 21% in men (e −0.238  = 0.788) and by 11% in women (e −0.113  = 0.893). Conclusions: In this study on Korean older adults, muscle mass did not have a direct effect on frailty but had an indirect effect through altered muscle function.